Body Weight, BMI, Percent Fat, Lean Mass and Their Long-Term Associations with Mortality and Incident Mobility Limitation. (29th May 2020) - Jonnalagadda, Satya; Harrison, Stephanie; Rogers-Soeder, Tara; Webber, Katey; Pereria, Suzette; Lane, Nancy; Cauley, Jane; Shikany, James; Farsijan, Samaneh; Langsetmo, Lisa; Cawthon, Peggy
Abstract: Objectives: Adiposity is often approximated by body mass index (BMI), weight, and % fat from dual energy x-ray absorptiometry (DXA). We aimed to describe how different measures of adiposity and body composition are similarly or differentially related to mobility limitation and mortality. Methods: Older community-dwelling men aged ≥65 yrs were followed for 10 years for mortality ( N  = 5849) and at six study contacts over 14 year for self-reported mobility limitations (any difficulty walking 2–3 blocks or with climbing 10 steps, N  = 5841). Baseline measures of adiposity included weight, BMI, % fat by DXA. Appendicular lean mass (ALM, by DXA) was analyzed as ALM/ht 2 . Proportional hazards models estimated the risk of mortality and repeated measures generalized estimating equations estimated the likelihood of mobility limitation. Adiposity and ALM/ht 2 measures were analyzed as quintiles and with splines. Results: Over 10 years, 27.9% of men died; over 14 years, 48.0% of men reported at least one mobility limitation. We observed U-shaped relationships between weight, BMI, % fat and ALM/ht2 with mortality. There was a log-linear relationship between weight, BMI and % fat with incident mobility limitation, with higher values associated with greater likelihood of mobility limitation: for those with the lowest values of each of these metrics (quintile 1), the likelihood of mobility limitation was 1.6 to 3.5 times greater than those with the highest values for these metrics (quintile 5, P  < .001 for all). In contrast, there was a U-shaped relationship between ALM/ht2 and incident mobility limitation. Conclusions: These observational data suggest that there is not a single weight, BMI or % fat value that can represent both the lowest risk of mortality and also the lowest likelihood for developing mobility limitation over time in older men. Funding Sources: National Institute on Aging and Abbott Nutrition.